PERBEDAAN KARAKTERISTIK KERTAS SENI DARI DAUN GLODOKAN TIANG KERING (Polyalthia Longifolia) KERING DENGAN TEKNIK PENGHALUSAN SECARA MANUAL DAN MACHINAL - Ningrum, Nidia Cahya Pratama; Triatma, Bambang (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2022)
Polyalthia longifolia is one of the plants that have roots that can with stand damage caused by vehicle vibrations that pass aroundit, so it is suitable to be used as a road shade plant. And can the dried leaves that fall can be used as raw materials for making handicraft products. This study will discuss the differences in the characteristics of an art paper with manual and machine smoothing techniques and see how the level of people's preference for art paper using experimental research methods and using the One Group Pretest-Postest research design. The dat a collection methodis observation and documentation, then the data results will be processed using percentage descriptive analysis. The results showed that the level of preference for the basic color of paper manually was 81.33% while manually 80%, cross-sectional contours of the paper were machined 76% while manually 78.66%, art paper texture was 69.33% while 74.66%, and the average tensile strength of paper manually is 57,552N, while manually is 25,506N and the average papere longation is 2,444% while the paper manually is 1,533%. When viewed from the characteristics, both paper shave their own advantages and disadvantages.